Studi Simulasi Pola Operasi Bukaan Pintu Bendung Gerak Mrican (Waru Turi) Kecamatan Gampangrejo Kabupaten Kediri Jawa Timur - Ramadian, Favian Giffary; Sayekti, Rini Wahyu; Sisinggih, Dian (Fakultas Teknik, Universitas Brawijaya, 2021)
The Mrican Weir (Waru Turi) is one of the largest motion weirs that dam the Brantas River. The weir irrigates the Waru irrigation area of 12,710 hectares and the Turi irrigation area of 16,444 hectares. The main function of the weir is to needs of irrigation water (flow control) and flood control structures. From a total of nine spillway gates, only eight gates are operating optimally. With the need for irrigation water that must be fulfilled, a new operating pattern is needed to continue to support this irrigation. The door opening operation pattern refers to the Normal Water Level at an elevation of +57.3 meters as the ideal reference. The water level receded at an elevation of +57.2 meters, and the Flood Water Level at an elevation of +58.28 meters. The simulation method for door opening (intake and spillway door) is based on irrigation requirements. With the gate opening simulation method, the maximum discharge of the spillway door (+57.3 m) is 63.67 m3/s, with an opening of 2.73 meters per door (a total of eight functioning gates). While at the Waru intake the discharge is 6.211 m3/s and Turi with a discharge of 7.936 m3/s, the maximum gate opening is 0.3 meters per door. With the new operating pattern, the discharge that flows at each intake gate still meets the needs of irrigation discharge.